Saliva leptin levels in tooth movement during initial stage of orthodontic alignment : a pilot study - Abu Bakar, Noraini; Mustafa Al-Ahmad, Basma Ezzat; Hilal Abbood Al-Bayati, Lina; Kamil, Wisam Alaa (2016)
During orthodontic tooth movement, the early response of periodontal tissues to mechanical stress is an acute inflammatory reaction. Mechanical stress from orthodontic appliances is believed to induce cells in the periodontal ligament (PDL) to form biologically active substances, such as enzymes and cytokines, responsible for connective tissue remodeling (Nishijima Y et al 2006). Leptin, a polypeptide hormone has been classified as a cytokine (Zhang et al 1994). Earlier findings suggested that leptin does play a significant role in bone formation by its direct effect on osteoblasts (Alparslan et al 2010). This pilot study aimed to study leptin in saliva and its association with tooth movement during initial orthodontic alignment. To determine if there is any difference in saliva leptin level before and after orthodontic alignment Ten orthodontic patients (7 girls and 3 boys; mean age, 16.76 ± 1.1 years) with crowding (up to 5mm) that required orthodontic fixed appliances, on a non-extraction basis as part of the treatment plan, were recruited in this longitudinal study. Orthodontic study models were constructed at baseline and at 6-weeks after orthodontic treatment commenced. Full fixed orthodontic appliances with initial 0.014” Nickel Titanium archwire placed. The amount of crowding was measured, before and after initial alignment. Unstimulated morning saliva sample were collected at all visits, after at least an 8-hour period of fasting and no-toothbrushing. The samples were tested using Leptin Abnova LEP Human ELISA kit and subsequently analyzed. Leptin concentration in saliva was significantly decreased in a time-dependant manner (p<0.001), from before orthodontic treatment (7016.45±425.15 pg/mL) and 6 weeks after bond-up (4901.92±238.64 pg/mL). Leptin concentration in saliva is decreased during orthodontic tooth movement in initial alignment stage.